Taxanes versus S-1 as the first-line chemotherapy for metastatic breast cancer (SELECT BC): an open-label, non-inferiority, randomised phase 3 trial. Issue 1 (January 2016) - Takashima, Tsutomu; Mukai, Hirofumi; Hara, Fumikata; Matsubara, Nobuaki; Saito, Tsuyoshi; Takano, Toshimi; Park, Youngjin; Toyama, Tatsuya; Hozumi, Yasuo; Tsurutani, Junji; Imoto, Shigeru; Watanabe, Takanori; et al.
Summary: Background: Oral fluoropyrimidines are used for the first-line treatment of metastatic breast cancer to avoid severe adverse effects, although firm supporting evidence is lacking. We aimed to establish whether S-1 is non-inferior to taxanes in this setting. Methods: We did an open-label, non-inferiority, phase 3 trial at 154 hospitals in Japan. We enrolled individuals who had HER2-negative metastatic breast cancer who had received no chemotherapy for advanced disease, and who were resistant to endocrine treatment. Patients were randomly assigned (1:1) either to taxane (docetaxel 60–75 mg/m 2 at intervals of 3–4 weeks; paclitaxel 80–100 mg/m 2 weekly for 3 of 4 weeks; or paclitaxel 175 mg/m 2 at intervals of 3–4 weeks) or to S-1 (40–60 mg twice daily for 28 consecutive days, followed by a 14-day break). Randomisation was done centrally with the minimisation method, with stratification by institution, liver metastasis, oestrogen and progesterone receptor status, previous treatment with taxanes or oral fluorouracil, and time from surgery to recurrence. The primary endpoint was overall survival, with a prespecified non-inferiority margin of 1·333 for the hazard ratio (HR). The primary efficacy analysis was done in the full analysis set, which consisted of all patients who took at least one study treatment and who had all data after randomisation. This trial is registered with the University Hospital Medical Information Network, Japan (protocol ID C000000416). Findings: Between Oct 27, 2006, and July 30, 2010, we enrolled 618 patients (309 assigned to taxane; 309 assigned to S-1). The full analysis set consisted of 286 patients in the taxane group and 306 in the S-1 group. Median follow-up was 34·6 months (IQR 17·9–44·4). Median overall survival was 35·0 months (95% CI 31·1–39·0) in the S-1 group and 37·2 months (33·0–40·1) in the taxane group (HR 1·05 [95% CI 0·86–1·27]; pnon-inferiority =0·015). The most common grade 3 or worse adverse events were neutropenia (20 [7%] of 307 patients in the S-1 group vs nine [3%] of 290 patients in the taxane group), fatigue (ten [3%] vs 12 [4%]), and oedema (one [<1%] vs 12 [4%]). Treatment-related deaths were reported in two patients in the taxane group. Interpretation: S-1 is non-inferior to taxane with respect to overall survival as a first-line treatment for metastatic breast cancer. S-1 should be considered a new option for first-line chemotherapy for patients with HER2-negative metastatic breast cancer. Funding: Comprehensive Support Project for Oncology Research of the Public Health Research Foundation, Japan; Taiho.